Kajian Sintesis Asam Lemak Hidroksamat Menggunakan Minyak Goreng Bekas - Muhsinun, Muhsinun (Jurnal Sains, Teknologi dan Kesehatan, 2024)
Fatty Hydroxamic Acids (FHA) has been successfully synthesized from used cooking oil. The purpose of this research was the enzymatic synthesis of fatty hydroxamic acids from used cooking oil and determine the optimum conditions, which includes three stages of processing, namely the oil preparation stage, the synthesis optimization stage and the characterization stage. At the oil preparation stage, the yield of used cooking oil was 29%. At the optimization stage, the optimum conditions for the synthesis of fatty hydroxamic acids from used cooking oil were at a temperature of 35oC for 25 hours with a ratio of lipase (gram) : hydroxylamine (mmol) equal to 1:500 and the ratio of lipase (gram) : crude bran rice (gram) was equal to 1:75. The number of hydroxamic acid groups in 1 gram of dry sample of fatty hydroxamic acid was 3,16 mmol. Based on the results of the analysis of the color test with Cu (II) and Fe (III), a complex color that is typical for the two metals which obtained with fatty hydroxamic acids, they were green and dark red. Whereas, from the FTIR analysis, the spectrum of the functional groups of hydroxamic acid was obtained.